PENINGKATAN DIGITAL LITERACY COMPETENCIES SISWA/SISWI SEBAGAI SMART DIGITAL CITIZENSHIP MELALUI PENYULUHAN INTERNET SEHAT DAN AMAN DI SMPN 3 JATIAGUNG LAMPUNG SELATAN - Arnila Purnamayanti; Sugiyanta Sugiyanta; Vina Karmilasari (Dharma: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this counseling is to improve the knowledge and understanding competence and digital literacy of the students of SMPN 3 Jati Agung, South Lampung on the importance of access and adoption of healthy and safe internet technology. The method used is counseling by the resource persons in which there are, measuring information literacy skills, providing education and training, interactive dialogue and monitoring. The result of this study is that the participants' mastery of healthy and safe internet counseling material experienced a significant increase from the low score before the training, which was only 54%, increasing to 94% in the very good category. In general, the increase can be concluded as 40%. Mastery of this concept can be demonstrated by participants in interpreting the concept of smart digital citizenship in the world of education, introduction of healthy and safe internet programs, internet etiquette culture, and safe digital-based information retrieval.